Prominent choroid plexus in meningomyelocele: sonographic findings. - Netanyahu, I; Grant, E G (American Journal of Neuroradiology, 1986)
Of 18 infants with meningomyelocele who were examined by cranial sonography, 17 were found to have a prominent choroid plexus, especially in the region of the glomus. In almost half of the cases this prominence assumed the configuration of a stalk arising from the glomus and terminating in a clublike ending. This prominence can be easily confused with intraventricular hemorrhage. The literature dealing with meningomyelocele and the Arnold-Chiari malformation makes no mention of this finding, but literature related to choroid plexus pathology describes similar findings in hydrocephalic infants, some of whom had documented meningomyelocele. This unusual choroidal configuration seen on sonography might be part of the spectrum of brain malformations seen in infants with meningomyelocele.